A 2007 Social Accounting Matrix for China - Zhang, Yumei; Diao, Xinshen (International Food Policy Research Institute, 2013)
This paper documents a 2007 Social Accounting Matrix (SAM) for China. This SAM was constructed for the China CGE model to assess the impact of the 2008-09 global recession shocks and the Chinese government's stimulus policy on China's economic growth. The SAM is constructed using data from various sources including an existing input-output table, national accounts, government budgets, balance of payments, commodity exports and imports, labor employment and wage statistics, household expenditure surveys and agricultural production statistics. Cross-entropy estimation techniques are used to balance the SAM. This SAM is a detailed representation of China’s economy in 2007. It covers 61 production activities and commodity sectors, 4 types of factors (low skilled labor, skilled labor, capital, and land), and 2 representative household (rural and urban) groups. The structural characteristics of China’s economy presented in the SAM would be helpful to better understand the economic linkages. And the SAM also provides an ideal tool for economy-wide impact assessments, such as a SAM-based multiplier analysis and computable general equilibrium (CGE) modeling.